2011
DOI: 10.1097/aln.0b013e318238bcf6
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based Assessment of Pediatric Anesthesia Skills

Abstract: Background: Assessment of pediatric anesthesia trainees is complicated by the random nature of adverse patient events and the vagaries of clinical exposure. However, assessment is critical to improve patient safety. In previous studies, a multiple scenario assessment provided reliable and valid measures of the abilities of anesthesia residents. The purpose of this study was to develop a set of relevant simulated pediatric perioperative scenarios and to determine their effectiveness in the assessment of anesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…The generalizability coefficient of 0.81 meets or exceeds that reported in comparable simulation-based assessment studies and high-stakes certification examinations (range, 0.56 to 0.80). 5,[30][31][32][33][34][35] Similar to previous investigations, 5,30,35 our results indicate that additional measurement precision could best be achieved by increasing the number of scenarios, and not the number of raters per scenario. The system design, based on multiple inputs regarding behaviors that are critical to safe performance, combined with the iterative development of detailed and anchored scoring rubrics, attention to scenario standardization, and methodical rater training, was effective in minimizing measurement errors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The generalizability coefficient of 0.81 meets or exceeds that reported in comparable simulation-based assessment studies and high-stakes certification examinations (range, 0.56 to 0.80). 5,[30][31][32][33][34][35] Similar to previous investigations, 5,30,35 our results indicate that additional measurement precision could best be achieved by increasing the number of scenarios, and not the number of raters per scenario. The system design, based on multiple inputs regarding behaviors that are critical to safe performance, combined with the iterative development of detailed and anchored scoring rubrics, attention to scenario standardization, and methodical rater training, was effective in minimizing measurement errors.…”
Section: Discussionsupporting
confidence: 87%
“…Previous simulation-based anesthesia studies also have documented widespread variability in performance both within and across practitioners with different levels of experience. 5,30,33,36,37 Others have demonstrated that learning curves differ among individuals, and that experience alone does not reliably lead to expertise without accompanying motivation, excellent teaching and feedback associated with practice, and focused environmental resources. [38][39][40][41] Although individual performance may be influenced by many factors, including motivation and realism of the simulated environment, large differences in performance within both resident and fellow groups, especially among individuals in the same or similar training programs, suggest the need for improved educational programs.…”
Section: Discussionmentioning
confidence: 99%
“…If we were to define acceptable reliability as at least 'substantial' level of agreement (i.e., ICC > 0.6), the predictive statistics show us that two raters would be required for each scenario (with some significant attention required to the procedures for the retained throat pack scenario, which would otherwise require three raters). Fehr et al (20) recently published their report of 35 anesthesia trainees participating in ten pediatric anesthesia simulation scenarios at a single institution. Six local faculty designed checklists for each of the ten scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…These element states cannot be directly determined, but must be assumed and iteratively solved until a valid combination that meets all criteria is found. The matrix form of the solution can be further defined by (11).…”
Section: Physics-based Circuit Solvermentioning
confidence: 99%
“…This is particularly true for emergency, military trauma, and critical care medicine. Simulation has been widely adapted in many areas of medicine, including anesthesia and trauma care and been shown to be highly effective in improving clinical confidence and skills [2][3][4][5][6][7][8][9][10][11]. Current training techniques include traditional didactic materials, virtual training scenarios, manikin simulations with and without physiology, and live patient simulations.…”
Section: Introductionmentioning
confidence: 99%